2011
DOI: 10.1007/s13659-011-0032-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of enzymes responsible for the reduction of geraniol to citronellol

Abstract: Abstract:The reduction of geraniol to citronellol is the first step for the synthesis of natural phytol in the production of tocopherols and natural vitamin K. Baker's yeast was used in the bioreduction described above as a whole-cell biocatalyst. However, the enzyme responsible for the reduction of geraniol to citronellol is not yet known. Four old yellow enzyme (OYE) genes were cloned from yeast and plants, and expressed in Escherichia coli for a high level of recombinant proteins. The recombinant protein di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Considering the structural homologies between these two compounds and geranial and citronellal respectively, we hypothesized that transformation of geraniol to citronellol included aldehyde intermediates and that Oye2p was involved in geranial to citronellal reduction. Recently, Yuan et al (2011) have shown that crude extracts of Escherichia coli cells expressing Oye2p are able to reduce geraniol into citronellol but in vivo activity has not been evidenced. Therefore we tested Oye2p and the homologous Oye3p for their possible involvement in geraniol to citronellol transformation in fermentation experiments.…”
Section: Oye2 Is Involved In Geraniol To Citronellol Reduction Duringmentioning
confidence: 99%
“…Considering the structural homologies between these two compounds and geranial and citronellal respectively, we hypothesized that transformation of geraniol to citronellol included aldehyde intermediates and that Oye2p was involved in geranial to citronellal reduction. Recently, Yuan et al (2011) have shown that crude extracts of Escherichia coli cells expressing Oye2p are able to reduce geraniol into citronellol but in vivo activity has not been evidenced. Therefore we tested Oye2p and the homologous Oye3p for their possible involvement in geraniol to citronellol transformation in fermentation experiments.…”
Section: Oye2 Is Involved In Geraniol To Citronellol Reduction Duringmentioning
confidence: 99%
“…1) (3,7,8). Such a conversion has been correlated with expression of 'old yellow enzyme' (Oye2) by yeast, which is an oxidoreductase responsible for the transformation step (9,10). The citrusy flavour perceived in beers is caused by the synergistic effect of geraniol and citronellol (11).…”
Section: Introductionmentioning
confidence: 99%
“…Using the purified recombinant PgOPR1-3, the double-bond reducing activity was first assayed with geraniol as a substrate. However, GC-MS analyses of the reactions detected no products, indicating that geraniol is not a substrate for PgOPR1-3, contrary to the previous report that H. brasiliensis OPR and yeast OYE2, structurally related to PgOPRs, could accept geraniol as a substrate [12]. We thus next assayed enzyme activity of PgOPRs with citral as substrate.…”
mentioning
confidence: 62%
“…This report provided a clue to the long-existing mystery of citronellol biosynthesis, but was rather surprising because OPR and OYE generally reduce double bonds adjacent to electronwithdrawing groups such as carbonyl groups [13]. Thus, geraniol, an allyl alcohol, did not seem to be a good substrate for OPR and OYE until Yuan's report was published [12]. However, if P. graveolens OPRs are also able to catalyze the geraniol to citronellol reduction, OPRs could be potential candidates for the citronellol biosynthetic enzyme in this plant.…”
mentioning
confidence: 99%
See 1 more Smart Citation